Business risk management handbook : - Spedding, Linda S. (CIMA, 2008)
It is now seen as essential that all businesses assess their exposure to business risk especially in relation to value creation. This book explains the practical links between risk management and the impact it has on the value of your business. It offers vital, accessible and timely tools to assist you in making an immediate difference to the core value of your business and thereby satisfy the demands of an ever increasing range of stakeholders.